2021
DOI: 10.1007/s13437-021-00240-4
|View full text |Cite
|
Sign up to set email alerts
|

Cybersecurity in the European Union port sector in light of the digital transformation and the COVID-19 pandemic

Abstract: The process of digital transformation, which is playing a fundamental role in the current COVID-19 worldwide panorama, has impacted all sectors of society, including the port sector. Albeit being a conservative sector, reluctant to change, it has been receptive to the opportunities offered by new information and communication systems and technologies, since they increase the efficiency of operation and, consequently, the competitive advantage of the port in the market. However, the digital era also brings new … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 13 publications
0
8
0
Order By: Relevance
“…Yet, the existing framework (Boh et al, 2023) lacks providing any information about changing roles and responsibilities in managing crises. Literature depicts that the recent crisis has urged organizations to change the roles and responsibilities of their employees due to cybersecurity issues (Bocayuva, 2021; Burrell, 2020). Therefore, the current study has explored and reported redefining roles, responsibilities, and tasks as a major dimension in the adaptation stage to manage the crisis effectively.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Yet, the existing framework (Boh et al, 2023) lacks providing any information about changing roles and responsibilities in managing crises. Literature depicts that the recent crisis has urged organizations to change the roles and responsibilities of their employees due to cybersecurity issues (Bocayuva, 2021; Burrell, 2020). Therefore, the current study has explored and reported redefining roles, responsibilities, and tasks as a major dimension in the adaptation stage to manage the crisis effectively.…”
Section: Methodsmentioning
confidence: 99%
“…Yet, the existing framework (Boh et al, 2023) lacks providing any information about changing roles and responsibilities in managing crises. Literature depicts that the recent crisis has urged organizations to change the roles and responsibilities of their employees due to cybersecurity issues (Bocayuva, 2021;Burrell, 2020).…”
Section: Justification For Adopting and Extending Digital Resilience ...mentioning
confidence: 99%
“…One of these unique outcomes is an accelerating trend towards remote business communication and information technologies. According to Bocayuva [8] , the pandemic accelerated digitalization, which in turn requires European Union ports to take strong measures against cyber-attacks.…”
Section: Literature Reviewmentioning
confidence: 99%
“… [49] Softening interstate and state-vessel relations on health crisis. [8] Information exchange and rising awareness of cyber-security is a vital issue on such pandemic crisis. [13] Study revealed that localization, near shoring, 3-D printing and teleworking activities could emerge for the near future.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Although the maritime sector has been traditionally conservative and reluctant to change, it has become increasingly receptive to the opportunities offered by new information and communication systems and technologies. This is because they improve operational efficiency, enhancing the port's competitive advantage in the market (Bocayuva, 2021).…”
Section: Introductionmentioning
confidence: 99%